Development of a real-time 3D audio headphone - Lou, Jing Ting (2016)
As there are more and more virtual reality entertainment applications such as 3D movie and 3D Game. Immersive audio is more important in nowadays to enhance the entertainment experience. But most existing immersive audio technology is based on loudspeaker system such as Dolby surround. There are essential playback differences between loudspeaker and headphone. Different to natural sound listening or loudspeaker playback listening, headphone is attached to the ear drum closely. Thus sound arrivals two ear drum at almost the same time and cause the Interaural time difference information loss. Another effect is the absent of environment rendering, human body rendering and partial of pinna rendering. In additional, sound is rendering by the inner shape of the headphone. All these would lead to Interaural level difference information change. Thus, a stereo or multi-channel record playback with headphone would be lack of rendering by the environment and human being’s bio signature such as pinna and head. In this project, a binaural audio method called Head-Related Transfer Function is used to reproduce realistic 3-D sound. The final system satisfy both real-time processing and plug and play.